Art on the Divide Line: Experiments in Art and Technology in India and Latin America - Thompson, Reynaldo (2022)
In this paper, we discuss the causes of regional variations in electronic art. Mapping regional achievements in electronic art requires understanding of resources of education and advancement of engineering in locations of economically productive cultures. If we think of development of algorithm as the driving cause of innovations in electronic media art we shall find that more regional niches are not lagging far behind – at least not in alternative market locations like India, or even China, although results are not so encouraging in Africa and the Eurasian countries.